Obstacles and Way Forward in Promoting Renewable Energy in Nigeria - Itodo, Isaac N. (Journal of Technology Innovations in Renewable Energy, 2014)
Nigeria is one of the world’s leading producers of crude oil and yet it is a net importer of refined oil. Its average daily premium motor spirit (PMS) consumption is 30 million liters. At 100% capacity the nation’s refineries will produce 17.74 million liters of premium motor spirit daily. A shortfall of over 10 million liters per day exists. Recent estimates stipulate that Nigeria requires 20,000 MW of electricity per annum. The projected electricity supply from all sources (conventional and renewable) in Nigeria in the short (2007), medium (2015) and long term (2025) is estimated to be 7000 MW, 14000 MW and 29,000 MW respectively. Annual peak electricity demand in Nigeria will increase from 4,558 MW to 45,755 MW in 2050 at high growth rate and 4,558 to 19,599 MW for low growth. Nigeria’s electricity per capita of 27 W/person is not enough to light an electric incandescent bulb of 30 W. These provide enough justification for the use of renewable energy in Nigeria. The use of renewable energy in Nigeria is hindered by the lack of regulation, financial incentives, energy infrastructures, framework for sustainability and technical expertise. Overcoming these obstacles will require invigorating research and development in renewable energy technologies, training and education to build local technical capacity, diversification of energy mix and scaling up of renewable energy utilization, aggressive capacity building in all areas of energy development and creation of enabling environment that will attract investment in energy infrastructure. This paper discusses the obstacles and way forward in promoting renewable energy in Nigeria.